Professors' formation and practices in an undergraduate nursing course - Vanessa Aparecida Ballista Tavares de Araújo; Raimunda Abou Gebran; Helena Faria de Barros (Universidade Estadual de Maringá, 2016)
Current research analyzes the formation and practices of professors in an undergraduate Nursing Course. The research consists of a case study investigated from an exploratory and descriptive aspect based on a qualitative approach. Ten successful faculty members from the Nursing Course were selected after prior survey among students, professors and management personnel. Semi-structured interviews, non-participant observations and documental analysis were conducted after the initial contact. Data discussion focused on Bardin's content analysis and the intepretation of the meaning of the answers given by the subjects, separated by categories, was employed. Analysis showed that successful professors entered the teaching career after professional practice in their respective fields; they seek pedagogical training, mainly through courses offered by the higher institution; they consider affection as a basic factor in the teaching-learning process; they aggregate procedures and techniques that allow greater participation and involvment of the students in the teaching and learning process. Current investigation will surely contribute towards the reshaping of qualitative formation of the professor-nurse.